The Allure of Flora Species Diversity in the Tropical Rainforest Ecosystem: the Need for Concern in a Global Context (Global Journal of Science Frontier Research, 2014)
There is no doubt that the tropical rainforest and its floristic richness is being faced with enormous challenges. The rainforest is being destroyed by man for various purposesagriculture, urbanization, fuelwood gathering and logging among others. Also, the increasing trend in the population structure of the people inhabiting the rainforest area has contributed significantly to its destruction. Thus, considering the inestimable value of the rich flora diversity of the rainforest, this paper therefore using relevant secondary sources of data tried to examine the rate of loss of the rainforest ecosystem and its rich flora diversity as well as examining the various forms of utilization of the flora species by the local people inhabiting the rainforest. So that their destruction becomes a very serious concern as there seem to be little or no effort to conserve these flora species for future generation.
Keywords: allure; species; ecosystem; rainfores